2022
DOI: 10.1186/s12864-022-08330-0
|View full text |Cite
|
Sign up to set email alerts
|

Complete genome sequence of biocontrol strain Paenibacillus peoriae HJ-2 and further analysis of its biocontrol mechanism

Abstract: Background Paris polyphylla is a herb widely used in traditional Chinese medicine to treat various diseases. Stem rot diseases seriously affected the yield of P. polyphylla in subtropical areas of China. Therefore, cost-effective, chemical-free, eco-friendly strategies to control stem rot on P. polyphylla are valuable and urgently needed. Results In this paper, we reported the biocontrol efficiency of Paenibacillus peoriae HJ-2 and its complete gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 89 publications
0
12
0
Order By: Relevance
“…The key gene in AI-2 QS system, luxS , and the four genes ( spo0A , spo0B , spo0F , and degU ) involved in biofilm formation pathway were found in genome of strain ZF390, and the sequence identity between ZF390 and HS311 (97.64%) exhibited higher values than those between strain ZF390 with SQR-21 (92.42%), HY96-2 (92.42%), or PS04 (91.06%). Key genes related to the plant-resistance inducers in ZF390 were retrieved in light of previous studies, and the identities of these genes among HS311, SQR-21, HY96-2, and PS04 were compared [ 7 , 56 ]. The results demonstrate that the key genes associated with volatile organic compounds belong to systemic resistance inducers, such as 2,3-butanediol, methanethiol, and isoprene synthesis, were all detected in the genomes of the five strains, with sequence identities exceeding 85% ( Supplementary Table S8 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The key gene in AI-2 QS system, luxS , and the four genes ( spo0A , spo0B , spo0F , and degU ) involved in biofilm formation pathway were found in genome of strain ZF390, and the sequence identity between ZF390 and HS311 (97.64%) exhibited higher values than those between strain ZF390 with SQR-21 (92.42%), HY96-2 (92.42%), or PS04 (91.06%). Key genes related to the plant-resistance inducers in ZF390 were retrieved in light of previous studies, and the identities of these genes among HS311, SQR-21, HY96-2, and PS04 were compared [ 7 , 56 ]. The results demonstrate that the key genes associated with volatile organic compounds belong to systemic resistance inducers, such as 2,3-butanediol, methanethiol, and isoprene synthesis, were all detected in the genomes of the five strains, with sequence identities exceeding 85% ( Supplementary Table S8 ).…”
Section: Resultsmentioning
confidence: 99%
“…Similar to Bacillus , the Paenibacillus species can be applied in agriculture as phytostimulators, biofertilizers, and bioagents. Paenibacillus strains have exhibited their biocontrol properties, including plant colonization, pathogen inhibition, plant-growth promotion abilities, and the activation of induced systemic resistance [ 6 , 7 ]. Previous studies revealed potential Paenibacillus biocontrol agents to protect plants from pathogens such as Phytophthora tropicalis , P. parasitica , Fusarium oxysporum , and Xanthomonas oryzae [ 8 , 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…The identities of different functional genes at the amino acid level were compared among the strains by using BLAST, with an E-value cut off of 1e-15 was used for the BLAST search ( Kumar et al, 2019 ). Secondary metabolite gene clusters were predicted by antiSMASH 4.0.2 ( Jiang et al, 2022 ).…”
Section: Methodsmentioning
confidence: 99%
“…Species in the genus Paenibacillus are either Gram-positive or variable, facultatively anaerobic or strictly aerobic, produce ellipsoidal endospores, and are nonpigmented, rod-shaped and motile ( Ash et al, 1993 ; Siddiqi et al, 2015 ). Currently, the genus Paenibacillus contains 240 species, including the plant-beneficial species of P. polymyxa ( Zhang et al, 2018 ; Timmusk et al, 2019 ), P. ehimensis ( Naing et al, 2015 ), P. alvei ( Emmanouil et al, 2016 ), P. macerans ( Liang et al, 2014 ), P. lentimorbus ( DasGupta et al, 2006 ) and P. peoriae ( Von der Weid et al, 2003 ; Jiang et al, 2022 ). Previously, P. peoriae was reported to act as a plant growth-promoting rhizobacteria (PGPR), which can produce biofilms, stably colonize the rhizosphere of plants and compete with other microbiota ( Von der Weid et al, 2003 ; Vejan et al, 2016 ; Jiang et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation